Analysis of the Effect of Word Of Mouth, Religiosity and Purchase Decisions of Alcoholic Beverages with Interest as a Mediation Variable - Cahyaning Tiyas Rahayu (Journal of Islamic Economic Laws, 2021)
This study aims to determine the effect of Word Of Mouth, Religiosity, on the decision to purchase alcoholic beverages in the Residency of Surakarta. This study found the factors that influence the decision to purchase alcoholic beverages in the Surakarta Residency. This research uses quantitative methodology to test the hypothesis. Statistical tests and data processing were carried out using Partial Least Square (Smart PLS 3.0). The research findings show that Word of Mouth has a significant and positive effect on purchasing decisions, religiosity has no effect on purchasing decisions, and word of mouth has a positive effect on purchase intention. Religiosity affects buying interest. Buying Interest has an effect on Purchase Decision.